Sleep apnea-COPD overlap syndrome is associated with larger left carotid atherosclerotic plaques - Landete, Pedro; Fernández-García, Carlos Ernesto; Muñoz, José M.; Friera, Alfonsi; Ancochea, Julio; González-Rodríguez, Águeda; García-Monzón, Carmelo (Frontiers in Cardiovascular Medicine, 2023)
BACKGROUND. Little is known about whether the overlap syndrome (OS) combining features of chronic obstructive pulmonary disease (COPD) and sleep apnea-hypopnea syndrome increases the risk of stroke associated with COPD itself. METHODS. We prospectively studied 74 COPD patients and 32 subjects without lung disease. Spirometry and cardiorespiratory polygraphy were used to assess the pulmonary function of the study population and ultrasound measurements of intima media thickness (IMT) as well as the volume of plaques in both carotid arteries were also evaluated. RESULTS. Polygraphic criteria of OS were met in 51% of the patients. We found that 79% of patients with OS and 50% of COPD patients without OS had atherosclerotic plaques in the left carotid artery (p=0.0509). Interestingly, the mean volume of atherosclerotic plaques was significantly higher in the left carotid artery of COPD patients with OS (0.07±0.02 ml) than in those without OS (0.04±0.02 ml, p=0.0305). However, regardless of the presence of OS, no significant differences were observed in both the presence and volume of atherosclerotic plaques in the right carotid artery of COPD patients. Adjusted-multivariate linear regression revealed age, current smoking and the apnea/hypopnea index (OR=4.54, p=0.012) as independent predictors of left carotid atherosclerotic plaques in COPD patients. CONCLUSIONS. This study suggests that the presence of OS in COPD patients is associated with larger left carotid atherosclerotic plaques, indicating that OS might be screened in all COPD patients to identify those with higher risk of stroke.